Significant Benefits of Nanoparticles Containing a Necrosis Inhibitor on Mice Testicular Tissue Autografts Outcomes - Del Vento, Federico (Int J Mol Sci, 2019)
Fertility preservation for prepubertal boys relies exclusively on cryopreservation of immature testicular tissue (ITT) containing spermatogonia as the only cells with reproductive potential. Preclinical studies that used a nude mice model to evaluate the development of human transplanted ITT were characterized by important spermatogonial loss. We hypothesized that the encapsulation of testicular tissue in an alginate matrix supplemented with nanoparticles containing a necrosis inhibitor (NECINH-NPS) would improve tissue integrity and germ cells’ survival in grafts. We performed orthotopic autotransplantation of 1 mm³ testicular tissue fragments recovered form mice (aged 4–5 weeks). Fragments were either non-encapsulated, encapsulated in an alginate matrix, or encapsulated in an alginate matrix containing NECINH-NPs. Grafts were recovered 5- and 21-days post-transplantation. We evaluated tissue integrity (hematoxylin-eosin staining), germ cells survival (immunohistochemistry for promyelocytic leukemia zinc-finger, VASA, and protein-boule-like), apoptosis (immunohistochemistry for active-caspase 3), and lipid peroxidation (immunohistochemistry for malondialdehyde). NECINH-NPs significantly improved testicular tissue integrity and germ cells’ survival after 21 days. Oxidative stress was reduced after 5 days, regardless of nanoparticle incorporation. No effect on caspase-dependent apoptosis was observed. In conclusion, NECINH-NPs in an alginate matrix significantly improved tissue integrity and germ cells’ survival in grafts with the perspective of higher reproductive outcomes.